CORRELATION AMONG THE EIGHTH GRADE STUDENTS' LEARNING MOTIVATION, PARENTS' INVOLVEMENT, AND ENGLISH SPEAKING SKILL AT SMP IT ISHLAHUL UMMAH PRABUMULIH - Kurniati Kurniati; Artanti Puspita Sari; Baginda Simaibang (Universitas PGRI Palembang, 2023)
This thesis is concerned with the inquiry on the correlations among students’ learning motivation, parents' involvement, and English speaking skill of the eighth grade students at SMP IT Islahul Ummah Prabumulih. The problem of the study is to investigate the correlation among students’ learning motivation, parents’ involvement, and English speaking skill. The total number of the population were 69 students. The sample for this study was 69 students. Data were collected by adopting a questionnaire for students’ learning motivation, parents’ involvement, and test for English speaking skill. Data were analyzed by using r-Product Moment and Multiple Regression. Finding show that there are correlations among learning motivation, parentss'involvement, and English speaking skill. The data analysis shows that R_yx1x2 = 0.978 with r^2=0.757 and p-Value is 0.000. This value is lower than 0.05. This is significant. So, Ha is accepted while Ho is rejected. Therefore, there are significant correlation among students' learning motivation, parents' involvement, and English speaking skill. Conclusions suggest that there are significant correlations among students'learning motivation, parents' involvement, and English speaking skill of the eighth grade students of SMP IT Ishlahul Ummah Prabumulih.